Employee Engagement, Satisfaction, and Commitment among BPJS Kesehatan Employees in 2024: A Quantitative Study - Prasetyo, Rizky Fajar; Wibhawa, Harie; Nurcahyo, Chandra; Kumalasari, Anggraeny; Gadistina, Welly; Syahputra Gani, Muhammad Yusuf; Arma, Sylvia; Nugraha, Mohammad Satria; Ramadhan, Aditya; Shaqylla, Sitti (Jurnal Jaminan Kesehatan Nasional, 2025)
This study analyzes employee engagement, satisfaction, and commitment among BPJS Kesehatan employees through an employee opinion survey in 2024. The survey conducted at BPJS Kesehatan showed positive results in several aspects but also identified areas that require attention. The Employee Engagement Index (EEI) reached 86.88%, indicating a high level of engagement, particularly among managerial positions. The Employee Satisfaction Index (ESI) also reached 87.77%, reflecting a very positive work environment for most employees. However, the survey found that 28.8% of employees experienced dissatisfaction, with excessive workload, policy changes, and organizational structural adjustments as the primary causes. Meanwhile, the Employee Commitment Index (ECI) reached 90.88%, showing strong commitment to the organization. This study emphasizes the importance of addressing employee welfare and recognition issues to significantly improve job satisfaction, especially in entry-level and mid-level positions. The survey reflects positive sentiment among BPJS Kesehatan employees regarding engagement, satisfaction, and commitment. However, it also highlights critical areas that need improvement to address dissatisfaction and enhance job readiness. By focusing on these areas, BPJS Kesehatan is expected to improve the overall work experience and productivity and create a more supportive work environment for all employees.